Numerical simulation of upper airway heat transfer in children with mandibular retrognathia during inspiratory process - Gao, Yikai; Liu, Hongyu; Liu, Na; Zhang, Li (Frontiers in Pediatrics, 2023)
The human upper airway regulates temperature, but its heating capacity remains unclear when the ambient temperature is low and the airway structure is abnormal. Therefore, the purpose of this study was to evaluate the heat transfer characteristics of the upper airway in patients with mandibular retrognathia, and to quantitatively evaluate the influence of ambient temperature on the temperature field of the upper airway, which could provide a valuable reference for the prediction, diagnosis and treatment of respiratory tract related diseases. Two typical ambient temperatures of -10 °C and 20 °C were selected to numerically simulate the air flow and heat transfer synchronization in the upper airway model of mandibular retrognathia under quiet breathing and heavy breathing. The results showed that the inspired air could not be sufficiently heated after flowing through the upper airway and main trachea in the two breathing states un-der low temperature conditions, and the inferior bronchus was more stimulated under the state of heavy breathing. In addition, the vortex flow structure in the upper airway can enhance the convective heat transfer effect in the corresponding area.